Effects of physostigmine on microcirculatory alterations during experimental endotoxemia - Peter, Christoph; Schmidt, Karsten; Hofer, Stefan; Stephan, Michael; Martin, Eike; Weigand, Markus A.; Walther, Andreas (Shock, 2010)
Microcirculatory dysfunction plays a pivotal role in the clinical development and manifestation of severe sepsis and as a marker for mortality. During this process, endothelial damage is characterized by structural and functional alterations that contribute to a great extent to tissue edema. Recent findings revealed the vagus nerve as an important transmitter of the cholinergic anti-inflammatory pathway. By inhibition of the cholinesterase, physostigmine increases acetylcholine and induces the cholinergic anti-inflammatory pathway. The aim of this study was to determine the effects of physostigmine on microcirculatory alterations during experimental endotoxemia. In male Wistar rats, venular wall shear rate, macromolecular efflux, and leukocyte-endothelial interaction were determined in mesenteric postcapillary venules using intravital microscopy at time 0, 60, and 120 min after beginning the experiment. The trials were divided into 2 parts. In part 1, we investigated the effects of physostigmine in a pretreatment setting where the animals in the treatment group obtained physostigmine (70 microg/kg) 15 min before starting endotoxemia (LPS, 2 mg/kg per hour). Part 2 of the experiment was a posttreatment setting, in which the effects of the application of physostigmine (70 microg/kg) 30 min after inducing endotoxemia were explored. In our study, we showed that macromolecular efflux and leukocyte-endothelial interaction were significantly reduced during endotoxinemia in the pretreatment and posttreatment settings with physostigmine. On the other hand, venular wall shear rate showed no differences. In summary, by inducing the cholinergic anti-inflammatory pathway, physostigmine reduced the capillary leakage and the leukocyte-endothelial interaction. The treatment with physostigmine in endotoxemia may be of interest for clinical use, and further studies should be performed.
Gesehen am 26.10.2022